COMMUNITY SERVICE ACTIVITIES THROUGH THE IMPLEMENTATION OF HEALTH EXAMINATION SERVICES AND COMPLEMENTARY THERAPIES: CUPPING AND ACUPUNCTURE - Ulfa, Ana Farida; Kurniawati, Kurniawati; Pujiani, Pujiani; Masruroh, Masruroh; Zuliani, Zuliani; Ghofar, Abdul; As’ad, Zulfikar; Farohiyah, Nuroin; Savika, Fanny Putri; Umami, VIna Riza; Prihartini, Sabrina Dwi (Caring: Jurnal Pengabdian Masyarakat, 2023)
Abstract A healthy society is the main ideal in health development in Indonesia. Complementary therapy has now become the main alternative for people seeking treatment, because it is considered cheaper and less painful. The aim of this activity is to provide health examination services and complementary therapy of cupping and acupuncture to the community in Mayangan Village, Jombang District. This activity consists of a health examination, implementation of complementary cupping and acupuncture therapy, administration of medication and health counseling. There were 80 participants who took part in this activity. Most of the participants in this activity were pre-elderly (57%), with the largest gender being female (66%). The age range of participants is relevant to the complaints that arise during the health examination. The most common complaints are bone pain (40%), headaches (20%) and tingling in the feet (34%). This is in accordance with the symptoms that appear in metabolic diseases. In theory, the aging process will cause changes in all body systems in the elderly, one of which is metabolic changes which cause complaints as mentioned above. Cupping therapy or acupuncture is relatively safe for all diseases and for the elderly. The comfortable response from participants after therapy shows that this therapy can be carried out continuously in the community.